2015
DOI: 10.1007/s00382-015-2895-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of boreal winter extratropical North Pacific Oscillation on Australian spring rainfall

Abstract: that caution is recommended regarding the Australian spring rainfall trend results obtained in this study as the austral spring rainfall trends may be sensitive to the choice of the selected time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The northern lobe of SLP in high latitudes extends from eastern Siberia to western Canada, while the southern lobe of SLP at lower latitudes includes the subtropics and extends equatorward to 20°N (Linkin & Nigam, 2008;Rogers, 1981;Walker & Bliss, 1932;Wallace & Gutzler, 1981). Furthermore, Song et al (2016) found that the boreal winter NPO has a pronounced influence on the subsequent Australian spring rainfall via air-sea coupled processes over the tropical Pacific. Furthermore, Song et al (2016) found that the boreal winter NPO has a pronounced influence on the subsequent Australian spring rainfall via air-sea coupled processes over the tropical Pacific.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The northern lobe of SLP in high latitudes extends from eastern Siberia to western Canada, while the southern lobe of SLP at lower latitudes includes the subtropics and extends equatorward to 20°N (Linkin & Nigam, 2008;Rogers, 1981;Walker & Bliss, 1932;Wallace & Gutzler, 1981). Furthermore, Song et al (2016) found that the boreal winter NPO has a pronounced influence on the subsequent Australian spring rainfall via air-sea coupled processes over the tropical Pacific. Furthermore, Song et al (2016) found that the boreal winter NPO has a pronounced influence on the subsequent Australian spring rainfall via air-sea coupled processes over the tropical Pacific.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, several studies have documented the influence of the NPO on the climate over East Asia, North America, and the tropical Pacific (Chen & Wu, 2017;Pak et al, 2014;Wang et al, 2007;Yeh & Kim, 2010;Yu et al, 2012). Furthermore, Song et al (2016) found that the boreal winter NPO has a pronounced influence on the subsequent Australian spring rainfall via air-sea coupled processes over the tropical Pacific. Therefore, it is useful to understand the variability in the NPO and its associated interactions in terms of extended-range predictions of weather and climate over the Pacific rim.…”
Section: Introductionmentioning
confidence: 99%
“…Once the data are detrended and the effect of ENSO removed, the authors find correlation coefficients in the range −0.35 to −0.48 (99% level) across the Northern Territory, Queensland, New South Wales, and Victoria. Song et al () suggest this link relates to NPO‐related sea surface temperature anomalies that drive anomalous Walker circulation that suppresses convection, reducing rainfall.…”
Section: Atmospheric Hazardsmentioning
confidence: 99%
“…Previous studies have demonstrated that Australian rainfall is influenced by many factors, such as Indian Ocean dipole (IOD; Saji et al, 1999;Ashok et al, 2003;Ummenhofer et al, 2011), Aleutian Low (AL; Zhu and Wang, 2010), North Pacific Oscillation (Song et al, 2015) and southern annular mode (SAM; Hendon et al, 2007). For example, Ashok et al (2003) found that the IOD has a significant negative correlation with rainfall over the western and southern regions of Australia.…”
Section: Introductionmentioning
confidence: 99%